A Miniaturized wide Stopband Low-pass Filter using T and Modified L Shapes Resonators - Fadaee, Mani D.; Shama, Farzin; Feali, Mohammad S.; Gilan, Maryam S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
A new structure of microstrip-based low-pass filter with wide stopband and sharp roll-off is introduced, in this paper. In the proposed topology, resonators with T and modified L Shapes have been used. To improve the suppression factor and relative stopband bandwidth, the second resonator has been added to the first resonator. The designed filter has been fabricated on a 20 mm thickness RO4003 substrate, which has a loss tangent of 0.0021 and a relative dielectric constant equal to 3.38. All parameters including roll of rate, stopband, bandwidth, return loss, insertion loss, and figure of merit have significant coefficients. Simulation has been ran using advanced design system software. The 3dB cutoff frequency is appropriate. The value of the insertion loss parameter is <0.1 dB and the S11 parameter is −22 dB at this point. The stopband is extended from 2.42 up to 24 GHz, which shows an ultra-stopband. The results of the simulation and experiment are almost similar, which indicates a proper performance of the designed structure.